2007
DOI: 10.1634/stemcells.2007-0065
|View full text |Cite|
|
Sign up to set email alerts
|

Disruption of Heparan and Chondroitin Sulfate Signaling Enhances Mesenchymal Stem Cell-Derived Osteogenic Differentiation via Bone Morphogenetic Protein Signaling Pathways

Abstract: Cell surface heparan sulfate (HS) and chondroitin sulfate (CS) proteoglycans have been implicated in a multitude of biological processes, including embryonic implantation, tissue morphogenesis, wound repair, and neovascularization through their ability to regulate growth factor activity and morphogenic gradients. However, the direct role of the glycosaminoglycan (GAG) sugar-side chains in the control of human mesenchymal stem cell (hMSC) differentiation into the osteoblast lineage is poorly understood. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 58 publications
5
61
0
Order By: Relevance
“…This observation is in agreement with previous reports showing that HS depletion by heparinase treatment or by knockdown of the PAPST, the transporter that transports PAPS from cytosol to Golgi for sulfation modification at HS biosynthesis, both attenuated BMP signaling in mESCs (29,44). Interestingly, Manton et al observed that HS depletion by heparinase treatment enhanced BMP signaling in human mesenchymal stem cells during differentiation into osteoblasts (48), indicating that HS functions to inhibit BMP signaling in the context of human mesenchymal stem cells. The positive and negative regulatory roles of HS in BMP signaling have been also observed during embryogenesis in EXT1-or NDST1-deficient mice, respectively (37,49).…”
Section: Discussionsupporting
confidence: 92%
“…This observation is in agreement with previous reports showing that HS depletion by heparinase treatment or by knockdown of the PAPST, the transporter that transports PAPS from cytosol to Golgi for sulfation modification at HS biosynthesis, both attenuated BMP signaling in mESCs (29,44). Interestingly, Manton et al observed that HS depletion by heparinase treatment enhanced BMP signaling in human mesenchymal stem cells during differentiation into osteoblasts (48), indicating that HS functions to inhibit BMP signaling in the context of human mesenchymal stem cells. The positive and negative regulatory roles of HS in BMP signaling have been also observed during embryogenesis in EXT1-or NDST1-deficient mice, respectively (37,49).…”
Section: Discussionsupporting
confidence: 92%
“…BMPs mediate their signals through phosphorylation of specific receptor-associated Smads, which then complex with other Smads, translocate to the nucleus, and affect gene transcription. We explored whether, under basal conditions, sFRP2 overexpression altered the transcript levels of BMP2, known to play a role in both osteogenic and chondrogenic commitment (12,13). Baseline relative transcript levels of BMP2 were similar in both groups (Fig.…”
Section: Sfrp2 Increases Msc Engraftment and Inhibits Canonical Wntmentioning
confidence: 99%
“…Canonical Wnt signaling directs osteogenic differentiation of MSCs by stimulating the expression of osteocalcin (10), this pathway is also involved in early chondrogenesis (11). The BMP pathway also modulates osteogenic differentiation of MSCs by controlling osteocalcin (12), and BMP2 induces chondrocyte fate determination (13). The Wnt cascade is involved in other cellular processes besides differentiation; canonical Wnt signaling inhibition, through the activity of Dkk-1, increases human MSC proliferation without overt differentiation (14).…”
mentioning
confidence: 99%
“…To confirm this, we treated MX2 matrices with heparinase I, II, III and chondroitinase ABC. Heparinase and chondroitinase are heparin sulfate and chondroitin sulphate degrading enzymes that cleave GAG chains [75].…”
Section: Discussionmentioning
confidence: 99%